A Cross-sectional Radiographic Study on the Effect of Vertical Malocclusions on Root Crown Ratio of Maxillary Teeth - G. V. D. Harsha; C. V. Padmapriya; Siva Kumar Arunachalam; D. P. K. Varma; Goutham Chakravarthy Vegesna; R. S. Usha Sree (Recent Developments in Medicine and Medical Research Vol. 3, 2021)
Introduction: Root resorption is the loss of apical root tissue caused by a decrease in the root-to-crown ratio. If not detected early, it usually spreads from the external surface to the pulp chamber. Several natural conditions put roots at risk of resorption in the absence of pathology. Knowing the pressure or aetiology of resorption will aid the orthodontist in treatment. In the Indian population, there is a scarcity of literature on root resorption caused by various malocclusions. Aim: To assess and validate the root crown ratios of maxillary incisors with vertical malocclusions and deleterious habits using two different radiographic techniques. Materials and Methods: 90 patients enrolled in orthodontic treatment were separated into three groups based on their nail biting habits: open bite, deep bite, and control. For maxillary incisors (360 teeth), panoramic radiographs and Periapical radiographs (by paralleling technique) were taken and traced. The root and crown lengths were measured, root crown ratios were determined, and the findings were converted to statistics using SPSS. Results: In both panoramic and periapical radiographs, a comparison of Root-crown ratios in vertical malocclusions revealed statistically significant (P < 0.001) differences in the Open bite group for all maxillary incisors. In the deep bite group, no statistically significant differences were found. A link was discovered between nail biting and the root-crown ratio. Gender preference was discovered to be absent. Conclusion: Decreased Root- crown ratios were noticed in open bite patients. Nail biting patients show significant root resorption. Root resorption can be assessed using both panoramic radiographs and periapical radiographs with the paralleling technique.